(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Rags are one of the traditional erasers to erase chalks on blackboards. When students and teachers use this, few students and teachers suffer from skin allergies and asthma. A vacuum eraser is available to prevent chalk dust allergies and asthma. This study aimed to study the students and teachers to help them teach with no problem. Quantitative research was used as the research design for the study, while purposive sampling was used to select respondents. Given that asthma and allergies are caused by chalk dust that can probably threaten the health of an individual, especially students and teachers, the use of a manually made propeller is inappropriate to create a vacuum eraser that can easily suck up chalk dust completely. Thus, the researchers replaced the manually made propeller with a build-in propeller that can work properly and can be used for easy collection of chalk dust. In terms of the body, the use of plywood was more preferable instead of illustration board because for the body to become presentable and durable. Having allergies and asthma has never been good for those students that use chalks to write on blackboards. Having an eraser that can help lessen the flow of chalk dust that can be easily used is important. Using 6 as length, 3 in as width, and2 in as its height will make the eraser extremely large. The researchers changed the size of the vacuum eraser to the length of 6 in, a width of 2.5 in, and a height of 2 in to become handy according to the recommendations of the respondents.